2012
DOI: 10.5712/rbmfc7(22)288
|View full text |Cite
|
Sign up to set email alerts
|

Perfil dos hipertensos da Unidade de Saúde da Família Cidade Nova 8, município de Ananindeua-PA

Abstract: A Hipertensão Arterial é um grave problema de saúde pública pela sua alta prevalência e morbimortalidade. Neste sentido, medidaspreventivas e corretivas são essenciais para o controle de agravos. Esta pesquisa teve como objetivo caracterizar o perfil clínicoepidemiológicodos hipertensos cadastrados em uma Unidade de Saúde da Família do município de Ananindeua, Pará. O estudo foi do tipoobservacional, transversal, descritivo e de natureza quantitativa. A coleta de dados foi realizada por meio da aplicação de um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 8 publications
1
5
0
11
Order By: Relevance
“…(10)(11)(12) The most common age in the study population was the range between 40 and 49, different from information found in the literature, which indicates that hypertension is prevalent in the male population of around 50 years old, and equating the female population after menopause. (6,7,11,12) This was observed in this study because it was based on record data rather than population survey, characterizing as a possible selection bias.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…(10)(11)(12) The most common age in the study population was the range between 40 and 49, different from information found in the literature, which indicates that hypertension is prevalent in the male population of around 50 years old, and equating the female population after menopause. (6,7,11,12) This was observed in this study because it was based on record data rather than population survey, characterizing as a possible selection bias.…”
Section: Discussionmentioning
confidence: 89%
“…In Brazil, this fact may be related to the increased availability of women to participate in activities developed in health services, in particular in the Family Health Strategy. (6)(7)(8)(9) Studies point to the fact that women seek treatment as a cultural reflection motivated by how the health services are organized (opening hours, location), and the higher life expectancy of women compared to men, which is attributed to cardiovascular protection and the lower consumption of tobacco and alcohol. (10)(11)(12) The most common age in the study population was the range between 40 and 49, different from information found in the literature, which indicates that hypertension is prevalent in the male population of around 50 years old, and equating the female population after menopause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudo congênere encontrou percentuais similares para o diabetes (22,7%) como comorbidade A análise do perfil sociodemográfico da amostra mostrou maior percentual de mulheres hipertensas, resultado semelhante ao de outros estudos [13][14][15][16] . A HAS apresenta uma prevalência global semelhante entre homens e mulheres, contudo, se apresenta elevada nos homens até os 50 anos, invertendo-se a partir da 5ª década 5 , fato que justifica os achados do presente estudo, uma vez que a população foi, em sua maioria, composta por indivíduos idosos.…”
Section: Resultsunclassified
“…A HAS apresenta uma prevalência global semelhante entre homens e mulheres, contudo, se apresenta elevada nos homens até os 50 anos, invertendo-se a partir da 5ª década 5 , fato que justifica os achados do presente estudo, uma vez que a população foi, em sua maioria, composta por indivíduos idosos. Além disso, há uma maior procura por serviços de saúde pelas mulheres que, consequentemente, acabam sendo mais diagnosticadas do que os homens 15 . O quantitativo de idosos se apresentou elevado.…”
Section: Resultsunclassified